Projekts - Gruzijas ražošanas uzņēmums. Modernizētu mašīnu ieviešana ar automatizācijas funkcijām - Ramishvili, Ani (Latvijas Universitāte, 2025)
The primary aim of this thesis is to develop a comprehensive, practical project plan that addresses the core operational inefficiencies in the manufacturing processes at Fabrica 1900— Georgia’s leading corrugated cardboard manufacturer. The aim is to propose a realistic, financially practical, and sustainable solution that reduces machine downtime, minimizes material waste, and modernizes the production line by integrating new machinery and automation systems.
Practical Project - Georgian Manufacturing Company. Implementation of Upgraded Machineris with Automation Features
Keywords: Ekonomika un uzņēmējdarbība; practical; manufacturing; MACHINERIES; AUTOMATION; cardboard